Private Solutions for Infrastructure in Honduras : A Country Framework Report - Public–Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
This document is designed to promote the development of infrastructure services in Honduras, with the aim of improving the country's competitiveness and contributing to poverty reduction. Its central argument is that Honduras needs a significant increase in private investment in infrastructure services, which should take place in a more competitive environment, and be subject to an adequate legal and regulatory framework. The study details the progress to date in Honduran infrastructure sectors, identifying the principal problems that exist and outlining a strategy for their solution. It proposes a general set of principles that should guide the provision of infrastructure services. In addition, it recommends specific policies for each sector. The document's scope includes the following services: transportation, water and sanitation, electricity, and telecommunications. Part 1 presents an overview of general themes related to the development of infrastructure services and to private participation in all the sub-sectors. Part 2 presents an analysis of the current situation of the four infrastructure services covered in this study. One of the major recommendations is the need to establish participative and transparent planning, and policy development processes so that policies are given legitimacy. The report also calls for strengthened regulation, and a rethinking on how to execute regulation, suggesting the creation of a sole regulatory entity. It suggests increased access is the key to reducing poverty, and that any subsidies should be oriented toward this end. It further discusses the potential role of private agents in achieving the improvements in quality and service needed to promote competitiveness, and, emphasizes the need to recoup the costs of services to make them sustainable. In this context, the report proposes a general framework to define the respective future roles of public and private agencies, as well as public and private financing, in the infrastructure sectors, while suggesting priorities for using public funds in the future development of the services.